Analisis Numerik Kuat Lentur Balok Support Beam Curve Tile Beton Semi Pracetak Dengan Variasi Panjang Bentangan - Yoga Ornando; Ismeddiyanto Ismeddiyanto; Iskandar Romey Sitompul (Sainstek (e-Journal), 2020)
Semi precast slab is a combination of precast concrete which consist of the support beam and curve tile with the cast in place concrete. During the working process, support beam will support the entire load until the slab becomes solid. The study aims to identify the effect of using variations of support beam length towards deflection-load relationship, moment-curvature, crack pattern and cross-sectional dimensions caused by pure bending moments with the same maximum load. The variations of the support beam length are L = 3000 mm, L = 4000 mm, L = 5000 mm and L = 6000 mm which can affect the cross-sectional dimensions of the support beam. The method used in this study was the numerical method by using Abaqus 6.14 CAE software. Abaqus is one of the finite element analysis (FEA) programs to model and analysis the elements of the structure. The loading applied was an axial load which has increased until the support beam failed. The numerical analysis results are the increase of cross section dimension as the increasing of support beam length. The cross-sectional dimension are 100 mm x 60 mm; 110 mm x 65 mm; 110 mm x 70 mm; and 115 mm x 75 mm. The maximum load (Pmaks) was relative same while the support beam length increased are 1,52 kN; 1,53 kN; 1,53 kN and 1,55 kN. The collapse pattern on the support beam was a pure bending crack at the most significant bending moment region. The crack pattern showed the crack on the pull side of the beam in the direction of the stirrups.